Ganciclovir Pharmacokinetics and Individualized Dosing Based on Covariate in Lung Transplant Recipients - Dvořáčková, Eliška; Šíma, Martin; Petrus, Jakub; Klapková, Eva; Hubáček, Petr; Pozniak, Jiří; Havlín, Jan; Lischke, Robert; Slanař, Ondřej (Pharmaceutics, 2022)
The aim of this prospective study was to evaluate the pharmacokinetics of ganciclovir in lung transplant recipients, to explore its covariates, and to propose an individualized dosing regimen. Ganciclovir was administered according to the protocol in a standardized intravenous dose of 5 mg/kg twice daily. Serum ganciclovir concentrations were monitored as a trough and at 3 and 5 h after dosing. Individual ganciclovir pharmacokinetic parameters were calculated in a two-compartmental pharmacokinetic model, while regression models were used to explore the covariates. Optimal loading and maintenance doses were calculated for each patient. In lung transplant recipients (n = 40), the median (IQR) ganciclovir total volume of distribution and clearance values were 0.65 (0.52-0.73) L/kg and 0.088 (0.059-0.118) L/h/kg, respectively. We observed medium-to-high inter-individual but negligible intra-individual variability in ganciclovir pharmacokinetics. The volume of distribution of ganciclovir was best predicted by height, while clearance was predicted by glomerular filtration rate. Bodyweight-normalized clearance was significantly higher in patients with cystic fibrosis, while distribution half-life was reduced in this subgroup. On the basis of the observed relationships, practical nomograms for individualized ganciclovir dosing were proposed. The dosing of ganciclovir in patients with cystic fibrosis requires special caution, as their daily maintenance dose should be increased by approximately 50%.
Keywords: lung transplant recipients; ganciclovir; covariates; cystic fibrosis; therapeutic drug monitoring